2022
DOI: 10.5455/annalsmedres.2021.09.562
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory markers used to predict mortality in severe COVID-19

Abstract: Purpose: In this study, we aimed to evaluate the laboratory markers used in the diagnosis of COVID-19 and to present the parameters that can be used to predict mortality. Material and method: The cases followed in the intensive care unit due to COVID-19 in our clinic between March 2020 and December 2020 were evaluated retrospectively. A total of 374 patients who met the study criteria were included in the study. The patients were divided into two groups as the patients who were discharged from the intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Infection markers such as white blood cell (WBC), sedimentation and C-reactive protein (CRP) are expected to be high in cases of COVID-19, which is already an infectious process. Studies have also shown the relationship between these values and mortality (18). Other reported main laboratory parameters included decreased platelet, lymphocyte, total protein levels, and increased D-dimer, creatinine, and creatine kinase levels (19).…”
Section: Discussionmentioning
confidence: 97%
“…Infection markers such as white blood cell (WBC), sedimentation and C-reactive protein (CRP) are expected to be high in cases of COVID-19, which is already an infectious process. Studies have also shown the relationship between these values and mortality (18). Other reported main laboratory parameters included decreased platelet, lymphocyte, total protein levels, and increased D-dimer, creatinine, and creatine kinase levels (19).…”
Section: Discussionmentioning
confidence: 97%